Invisible Labor, Sacred Narratives: The Paradox of Protection and Exploitation of Women Migrant Workers in Saudi Arabia - Umar Sheikh Tahir (LPPM IAIN Parepare, 2026)
This study investigates the contradiction of protection and exploitation faced by female migrant workers in Saudi Arabia from a socio-religious perspective. Although formal labour frameworks prioritise safety, workers often face constraints that hinder mobility, communication, and autonomy in household environments. The study utilises qualitative data from 42 individuals, comprising migratory workers and institutional actors, and adopts a multi-country methodology to elucidate variances between sending contexts. Findings indicate that protective mechanisms frequently operate as instruments of control integrated into structural and relational dynamics. Sacred narratives serve a twofold purpose: they legitimise employer authority and furnish workers with coping mechanisms and ethical foundations for negotiating. The research indicates that agency is manifested through quotidian practices including strategic compliance, relational bargaining, and informal networking. The research enhances current frameworks on migrant labour and gender by incorporating structural, cultural, and religious factors. It enhances multidisciplinary discussions by elucidating the intersections of meaning, power, and vulnerability within international labour contexts. The study closes by highlighting the necessity for more comprehensive and contextually aware strategies for the protection of migrant workers that consider both institutional and socio-cultural elements.